2023
DOI: 10.1177/03635465221145939
|View full text |Cite
|
Sign up to set email alerts
|

Age, Sex, and BMI Differences Related to Repairable Meniscal Tears in Pediatric and Adolescent Patients

Abstract: Background: The incidence of meniscus tears and ACL tears in pediatric patients continues to rise, bringing to question the risk factors associated with these injuries. As meniscus tears are commonly repaired in pediatric populations, the epidemiology of repairable meniscus tears is an important for consideration for surgeons evaluating treatment options. Purpose: To describe meniscal tear patterns in pediatric and adolescent patients who underwent meniscal repair across multiple institutions and surgeons, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This is the rationale behind studies that encourage early postoperative weight-bearing in longitudinal tears, such as bucket-handles, but not in radial tears [47]. These findings suggest that complex lesions, usually treated with a meniscectomy and representing up to 18% of meniscal injuries in pediatrics, could be treated with the adhesive patch using the meniscus wrapping method [48]. Adhesive hydrogels could represent a treatment method for tears in the red-red zone because of their mechanical edge-holding effect, but we believe that tears in the white-white zone could also be treated with the biological augmentation of the patch.…”
Section: Discussionmentioning
confidence: 99%
“…This is the rationale behind studies that encourage early postoperative weight-bearing in longitudinal tears, such as bucket-handles, but not in radial tears [47]. These findings suggest that complex lesions, usually treated with a meniscectomy and representing up to 18% of meniscal injuries in pediatrics, could be treated with the adhesive patch using the meniscus wrapping method [48]. Adhesive hydrogels could represent a treatment method for tears in the red-red zone because of their mechanical edge-holding effect, but we believe that tears in the white-white zone could also be treated with the biological augmentation of the patch.…”
Section: Discussionmentioning
confidence: 99%
“…Rohde [ 9 ] found that meniscal injuries usually occur in a higher population of obese patients by retrospectively analyzing 1185 cases of meniscal injuries in a population of children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 8 ] Some studies have suggested that obese subjects may be more prone to meniscal injuries than normal weight subjects, but conclusions have been mixed. [ 9 , 10 ] Therefore, the causal relationship between obesity and meniscal injuries still needs further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…These and other recent AJSM publications that focused on adolescents demonstrate the current keen research interest in this age group, in which intense athletic activity combines with rapid musculoskeletal development and labile psychosocial dynamics to create a challenging treatment environment. 8,9,12,15,17,19,20 Continuing clinical research will help surgeons and other sports medicine practitioners provide more knowledgeable guidance and greater treatment success for patients as they navigate this exciting yet intimidating stage of life.…”
mentioning
confidence: 99%